Implementation of Digital Scientific Literacy in Family Education (Gender Study in Remote Areas of South Sulawesi) - Syamsuni Syamsuni HR; Jumadi Jumadi; Aisyah Nursyam; Besse Nurul Kafilawaty (Postgraduate, University of Mataram, 2024)
: Gender is a crucial aspect in problem-solving within families that can influence a child's social activities in society. Globally, there are disparities between males and females in accessing Digital Scientific Literacy. Access to Digital Scientific Literacy is predominantly observed in urban areas and utilized within the family education context. This study aims to investigate the implementation of family education using the scientific approach, employing the 5M pattern: Observing, Questioning, Trying, Reasoning, and Communicating. The study utilized a Mixed Methods approach involving 100 households, consisting of 80 boys and 80 girls, in remote areas of South Sulawesi. Findings reveal that the application of family-based education rooted in Digital Scientific Literacy remains suboptimal. This is attributed to a lack of parental comprehension regarding Scientific Literacy in remote areas of South Sulawesi. The predominant role in educating children within the family lies with the mothers, while fathers mainly reinforce the implementation of family education. Additionally, there exists a disparity between boys and girls in accessing Digital Scientific Literacy, with boys demonstrating a higher dominance in this domain.